Bactérias fecais em ostras, Crassostrea rhizophorae - Silva, Ana Isabel Mota (2003)
Oysters are filter-feeding organisms which can accumulate high concentrations of microorganisms. This study is aimed to evaluate the microbiological quality of oysters from a natural growing site located at the Cocó river, Fortaleza, Ceará State, Brazil. An estimate of Most Probable Numbers (MPN) of Fecal Coliformss (FC) was performed, and the presence of Salmonella was tested. The values of MPN of Fecal Coliforms ranged between <1.8 and 920 per gram. Salmonella was found to occur in 21 of 30 tested samples (70%).